Evaluation of laboratory request forms submitted to clinical pathology department in tertiary health care hospital - Manoharan, Kavitha; Manoharan, Hemavathi; Sharma, Chetna (International Journal of Research in Medical Sciences, 2019)
Background: Laboratory diagnostics is the fast-growing field which contributes 70% of clinical diagnosis. Laboratory information has a profound impact on patient diagnosis. Research has demonstrated most of the laboratory errors occur in the pre-analytical phase. Incorrect and incomplete filling of information on the laboratory request forms can significantly impact the quality of laboratory results, and it affects patient outcome and resources. We, therefore, evaluated the extent of incomplete laboratory forms in our center. Methods: The study was a retrospective study conducted on all request forms received over 1 month from June 15, 2018, to July 15, 2018, in the Clinical Pathology Department of ESI hospital, Coimbatore, during working hours were analyzed for the frequency of incomplete data. Results: Only the patient’s name appeared in all the forms. Consultant in charge of requesting laboratory tests (99%) was the most omitted parameter. No clinical details or location/ward details of the patient was provided in 90.7% and 7% of the cases. Age and gender did not appear in 21.9% and 22%, respectively. Date of request, doctor’s signature, and hospital number were missing on 8.4%, 27.6%, and 4.4%, respectively. Conclusions: The study has demonstrated the level completion of laboratory request forms was suboptimal. This may be responsible for many pre-analytical errors. There should be closer interaction between clinicians and laboratory physician to improve the quality of laboratory services and resource management.